Estudo sobre a produção habitacional e as mudanças nos preços de moradias em Belo Horizonte entre 2009 e 2022 - Ícaro Neri Pereira de Souza (2023)
Based on critical reflections on the dynamics of capital accumulation, this study addresses the relationships between housing production, space production, and social class movements in Belo Horizonte. The construction of this work stemmed from the conjunction of two approaches in geographical thinking: a Marxist critique aimed at reflecting on the main characteristics of housing, space, and city production in Brazil (a country situated peripherally and dependent within global capitalism, and highly unequal), including its specificities in Belo Horizonte; and, through data analysis, the use of GIS and statistical software, a cartographic and theoretical-quantitative approach that allowed for empirical findings. Processes such as spatial and market patterns of housing production, the formation of real estate vectors, and socio-spatial phenomena associated with these changes in housing prices and social class movements in the city were analyzed. The methodology involved spatialization and processing of data from over 240 thousand apartment transactions and 40 thousand house transactions in Belo Horizonte, obtained from data tabulation by the Belo Horizonte City Hall (PBH) on the payment of the Real Estate Transfer Tax (ITBI). Data analysis included the creation of graphs, tables, and maps to describe and map the observed transaction patterns. Spatial dependency, spatial association, and cluster analyses were also conducted to identify existing socio-spatial transaction patterns in the city. The results revealed a significant increase in housing prices in the initial years considered in the study, followed by a general stagnation with substantial losses due to inflation. Related to the national economic dynamics, these movements highlighted the significant role of liquidity in price changes. Regarding spatial aspects, the research mapped the pattern of spatial self-segregation related to prices per square meter and access to housing itself, as well as the formation of pericentral axes with average housing prices higher than those in peripheral areas of the city, with these pericentral vectors mainly occupied by individuals and families of middle classes. These axes expanded over previously impoverished areas, such as the Barreiro region, and also with the occupation of large "urban voids" with housing dedicated to populations of middle to high incomes. With these observations, we reflect on the movement of profit rates in the urban space of Belo Horizonte, the nature of the urban structuring/restructuring process, and gentrification processes in the city. In our view, Belo Horizonte has further consolidated and expanded the primary nature of its production since its inception: the expulsion of poverty to increasingly distant peripheries through the generation and expansion of socio-spatial differentiations.